RELATIONSHIP BETWEEN AGGRESSION AND ACADEMIC ACHIEVEMENT AMONG STUDENTS IN SECONDARY SCHOOLS - Miringu Kibe, Henry; Owaa, Judith; A. Raburu, Pamela (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
The number of students quitting school before passing their matriculation examination is a major cause for concern. A highly qualified workforce is necessary due to the acceleration of technological advancement and the emergence of new, more challenging job prospects. Since underachievement hinders the growth of the labor force, it follows that each student should be encouraged to perform at his best level. With a perfect school environment, there are better chances of a better performance. However, many students in Kenya particularly, Githunguri Sub-County, whose performance has been very low, and the underlying Social Adjustment Indices that influence their Academic Achievement at secondary school have not received appropriate research. Determining the Influence of Social Adjustment Indices on Academic Achievement among students in public secondary schools in Githunguri Sub-County, Kenya, was the main goal of the current study. Among students in public secondary schools in Githunguri Sub-County, the following objectives was set to establish the relationship between aggression and academic achievement; to find out the relationship between social withdrawal and academic achievement. Social learning and classical conditioning theory were both used in the study. Utilizing Creswell's mixed method technique, concurrent embedded research design was used. The selection of the participating schools and students was done using stratified random, purposive, and saturation sampling procedures. A population of 2787 students, 38 deputy principals, and 38 teachers of guidance and counseling were selected for the study from which 350 form two students, 15 deputy principals, and 15 instructors of guidance and counseling made up the study sample. For data collection, the present study included questionnaires, interview schedules, and document analysis. A pilot study was carried out using 35 form two students from four public secondary schools in the Githunguri Sub-County. Two specialists from Jaramogi Oginga Odinga University of Science and Technology verified the validity of the instruments. By using Cronbach's alpha, internal consistency was employed to determine the instrument's reliability, and a reliability coefficient above 0.7 was found. The Statistical Package for Social Sciences (SPSS) version 22.0 was used to examine quantitative data. Inferential statistics involved Pearson Product Moment correlation coefficient, simple and multiple regression analysis, and ANOVA, and descriptive statistics covered frequency counts, percentages, averages, standard deviation, and variance. Hypotheses were evaluated at a 5% level of significance. Thematic analysis was employed to examine qualitative data. The results showed a somewhat negative association between Aggression and Academic Achievement (n=308, r = -.568; p.05. According to the present study's findings, Social Adjustment Indices should be incorporated into school guidance and counseling policies and practices since they have a major impact on academic attainment.